LEARNING FOREIGN LANGUAGES WITH THE HELP OF THE INTERNET: INNOVATIONS, STRATEGIES, AND TOOLS - Nazarboyeva Marjona Azimboy qizi; Atajanova Nazokat Mansur qizi (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
In the digital age, the internet has revolutionized many aspects of human life, including education. One of the most prominent changes can be seen in the way people learn foreign languages. This article explores the role of the internet in facilitating foreign language learning, highlighting the various online resources, strategies, and technological tools that have transformed traditional language acquisition processes. It evaluates the effectiveness of e-learning platforms, social media, online communication tools, mobile applications, and virtual reality technologies in enhancing linguistic competence. Furthermore, the article examines the advantages and challenges associated with internet-based language learning and offers practical recommendations for learners and educators to optimize the process. Based on academic research, real-life examples, and pedagogical principles, the article concludes that the internet, if used strategically, can significantly boost language acquisition in both formal and informal contexts.